2021
DOI: 10.5194/essd-13-4437-2021
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and discussion of the high-resolution atmosphere–land-surface–subsurface simulation dataset of the simulated Neckar catchment for the period 2007–2015

Abstract: Abstract. Coupled numerical models, which simulate water and energy fluxes in the subsurface–land-surface–atmosphere system in a physically consistent way, are a prerequisite for the analysis and a better understanding of heat and matter exchange fluxes at compartmental boundaries and interdependencies of states across these boundaries. Complete state evolutions generated by such models may be regarded as a proxy of the real world, provided they are run at sufficiently high resolution and incorporate the most … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Furthermore, a 3D geologic model of the geological survey of Baden-Württemberg defined by 11 rock types was used, which should provide a realistic representation of the deeper subsurface of the domain. Using this setting, Schalge et al (2021) demonstrated that the simulated GWL and river discharge were in good correspondence with the observed values.…”
Section: The Vr As a Reference Modelmentioning
confidence: 66%
See 2 more Smart Citations
“…Furthermore, a 3D geologic model of the geological survey of Baden-Württemberg defined by 11 rock types was used, which should provide a realistic representation of the deeper subsurface of the domain. Using this setting, Schalge et al (2021) demonstrated that the simulated GWL and river discharge were in good correspondence with the observed values.…”
Section: The Vr As a Reference Modelmentioning
confidence: 66%
“…Using this setting, Schalge et al. (2021) demonstrated that the simulated GWL and river discharge were in good correspondence with the observed values.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…For our test, we were provided observations from 25 ground water measuring sensors distributed over the whole catchment. Observation values were taken from a virtual reality simulation (Schalge et al, 2020). ParFlow runners are parallelized on one full node (40 processes for experiments on Jean-Zay and 48 processes for JUWELS, respectively).…”
Section: Experimental Studymentioning
confidence: 99%
“…The simulations span a region of 267 km × 302 km in longitudinal and latitudinal direction, respectively, located in the south-western part of Germany with the embedded Neckar catchment. As similarly used in Schalge et al (2021), the heterogeneous land surface setup typifies conditions in mid-latitudes and Central Europe. The lateral boundary conditions in the atmosphere are based upon one member of the COSMO-DE-EPS ensemble (Peralta et al, 2012) with a similar configuration to our atmospheric setup.…”
Section: Modelmentioning
confidence: 99%